Distributive conflict, economic policy, and macroeconomic volatility in Argentina (1890-2020) - Catelén, Ana Laura (2026)
For decades, Argentina's long-run divergence has intrigued economic historians. While by the late nineteenth century the country ranked among the world's richest economies, it now occupies a middle position in the global income distribution (Bolt and van Zanden, 2020). A distinctive feature of Argentina's experience, relevant for explaining this outcome, is the marked rise in macroeconomic volatility since the mid-1970s. Unlike other South American economies, this instability has intensified over time (Catelén, 2025), and elevated volatility undermines long-run growth (Badinger, 2010; Loayza & Hnatkovska, 2004; Pastor, 2017; Ramey & Ramey, 1994). Latin American structuralist theory provides a useful framework to understand why volatility itself becomes persistent through the emergence of vicious cyclical dynamics. These dynamics involve recurrent interaction processes that amplify and prolong fluctuations. A central mechanism in this approach is structural distributive conflict, defined as the gap between workers' wage aspirations and the economy's productive capacity (Rapetti & Gerchunoff, 2016). This paper revisits this theoretical tradition and combines it with a modern empirical approach based on a structural VAR framework that allows for causal interpretation to assess whether the interaction between distributive conflict and economic policy can account for Argentina's recurrent cycles of instability that undermine long-run growth. The analysis examines the historical evolution of distributive conflict across three development regimes (the agro-export model, state- led industrialization, and the second globalization) within a structuralist framework linking external constraints, distributive conflict, and macroeconomic instability.